2008
DOI: 10.1111/j.1365-2788.2008.01100.x
|View full text |Cite
|
Sign up to set email alerts
|

What clinical characteristics of children with autism influence their inclusion in regular classrooms?

Abstract: The time spent in special-intervention services and regular classrooms combined did not add up to an adequate number of weekly hours for these children, particularly those exhibiting at least one of the following characteristics: low adaptation level, major behavioural problems or low socioprofessional category of parents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 29 publications
2
17
0
8
Order By: Relevance
“…Similarly, nearly half (49.8%) reported that it is necessary to remove students with autism from the regular education classroom in order to meet their educational needs. This is consistent with Yianni-Coudurier et al (2008) who found that the clinical characteristics of autism influenced student placement within the regular education classroom. Teachers were supportive of inclusion yet student time within the regular education settings was noted to decrease as severity of autistic symptoms and aberrant behaviors increased.…”
Section: Resultssupporting
confidence: 90%
“…Similarly, nearly half (49.8%) reported that it is necessary to remove students with autism from the regular education classroom in order to meet their educational needs. This is consistent with Yianni-Coudurier et al (2008) who found that the clinical characteristics of autism influenced student placement within the regular education classroom. Teachers were supportive of inclusion yet student time within the regular education settings was noted to decrease as severity of autistic symptoms and aberrant behaviors increased.…”
Section: Resultssupporting
confidence: 90%
“…8,9 These cooccurring behavioral problems pose enormous challenges to parents, may result in restrictive school placement, and undermine interventions in the home and community. 10 Disruptive behavior may actually contribute to adaptive skill deficits. A child's active protest in response to parental efforts to promote daily living skills may compel parents to complete the task to avoid conflict.…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that there are distinct adaptive skills trajectories in the cohort which are not linear through time. Moreover, given the disparities in autism services in our country (Yianni-Coudurier et al 2008) we expect that a more intensive treatment will be related to a better outcome and a better socioeconomic status.…”
Section: Introductionmentioning
confidence: 99%